The Aura of Africanness in Ola Rotimi’s drama - Olorunsomo, Adeniyi Temitope; Zaccheaus, O. J. (NIU Journal of Humanities, 2018)
The term  "African Drama" connotes a play in performance about African people in social, economic, or political interaction .Beginning with the seminal, The gods are not to blame (1975) which many acknowledged was patterned after the Greek prototype-Oedipus, The King. Rotimi made a conscious attempt at indigenizing his drama and theatre through the matrix of African culture and philosophy. This paper is a study of the Africanness of Ola Rotimiâ€™s drama through three of his selected plays: The gods are not to blame (1971), Ovonramwen Nogbaisi (1974) and Hopes of the Living Dead (1987). From the standpoint of theatre as a reflection of societal realities, the study will explicate Rotimiâ€™s abiding engagement with Africa and African issues through the themes, languages and character expositions, coming to the logical conclusion that the plays are African drama in European skin.   Keywords :  African Literature, Aura, Africaness, Drama, Theatre.